The effect on trial and purchase behaviour of mail-drop product sampling and purchase incentives among non-users : a thesis prepared in partial fulfilment of the requirements for the degree of Master of Business Studies at Massey University - McGuinness, Dalton Erin (Massey University, 1992)
Escalating expenditure on sales promotion techniques has lead to increasing concern over their effectiveness . Techniques such as product sampling and purchase incentives are widely believed to encourage new trial and purchase behaviour among non-users, but few studies have verified this belief empirically. This thesis reports the results of three pioneering experiments that examine the effectiveness of mail-drop product samples, coupons, and cash-backs, as means of promoting new trial and purchase behaviour among non-users of three brands: a laundry detergent, an instant coffee, and a new toothpaste variant. A sample of 800 households was randomly selected and, for each product, households were assigned to one of four treatment groups: sample plus coupon, sample only, coupon only, and a control group. Trial and purchase data were obtained from 493 households after over two telephone interview waves. The results indicated that samples achieved much higher rates of new trial and purchase behaviour than coupons. Coupons and cash-backs delivered alone were found to be ineffective means of encouraging purchase behaviour among non-users, and including them with samples only had a marginal, if any, effect on purchase behaviour. This study has important implications for the practice of sampling and couponing. In particular, coupons may only subsidise purchases that would otherwise be made at full retail prices, which suggests that the current industry practice of providing coupons with samples may be unwarranted.
Keywords: Advertising; Samples (Commerce)